Zürcher SAJ-Gruppe im Oktober 1939 - Risler, Robert
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Sozialismus